2005
DOI: 10.1111/j.1365-3121.2004.00590.x
|View full text |Cite
|
Sign up to set email alerts
|

A review of the Irish crustal structure and signatures from the Caledonian and Variscan Orogenies

Abstract: This paper reviews the complex crustal and upper-mantle seismic velocity structure of Ireland and surrounding seas. Data from 11 seismic refraction profiles reveal that onshore Ireland mean crustal velocities range between 6.25 and 6.5 km s )1 with crustal thickness of 28.5-32 km. Superimposed on a threelayer crust, the sedimentary layer has a thickness of approximately 6-8 km at the southern coastline, but only 3-4 km in the vicinity of the Shannon Estuary in western Ireland. The lateral heterogeneity of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 29 publications
2
34
0
Order By: Relevance
“…5b) are plotted in Figure 8a as a percentage of the unstretched thickness of the Flemish Cap and the Irish crust (30 km; Funck et al 2003 andLowe &Jacob 1989 respectively). Whereas the unstretched crustal thickness for the Irish crust is generally consistent at 30 km for the entire margin (Lowe & Jacob 1989;Vogt et al 1998;Landes et al 2005;O'Reilly et al 2006;Ziegler & Dèzes 2006), the broader crustal thickness variability for the offshore Newfoundland margin (30 and 36 km beneath Flemish Cap and the Grand Banks respectively; Funck et al 2003 andLau et al 2006a), means that the crustal thickness percentages on the Grand Banks, which are not the focus of this comparison study, occasionally exceed 100% in Figure 8a.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…5b) are plotted in Figure 8a as a percentage of the unstretched thickness of the Flemish Cap and the Irish crust (30 km; Funck et al 2003 andLowe &Jacob 1989 respectively). Whereas the unstretched crustal thickness for the Irish crust is generally consistent at 30 km for the entire margin (Lowe & Jacob 1989;Vogt et al 1998;Landes et al 2005;O'Reilly et al 2006;Ziegler & Dèzes 2006), the broader crustal thickness variability for the offshore Newfoundland margin (30 and 36 km beneath Flemish Cap and the Grand Banks respectively; Funck et al 2003 andLau et al 2006a), means that the crustal thickness percentages on the Grand Banks, which are not the focus of this comparison study, occasionally exceed 100% in Figure 8a.…”
Section: Discussionmentioning
confidence: 88%
“…Despite the mosaic of underlying basement terranes, there appears to be no clear regional correlation between crustal thickness and the nature or boundaries of the basement terranes on the Irish margin. A 30 km thick crust is observed beneath Ireland across a range of basement types and structures (Lowe & Jacob 1989;Landes et al 2005;Ziegler & Dèzes 2006). The crust is similarly 30 km thick beneath the Porcupine Bank (O'Reilly et al 2006) and the Rockall Bank (Vogt et al 1998).…”
Section: Tectonic Settingmentioning
confidence: 97%
“…Deep seismic experiments, summarized by Landes et al (2005), record variations in Moho depth and anomalously low middle and lower crustal Pwave velocities (Lowe & Jacob, 1989), which may reflect a change in basement composition. Deep seismic reflection studies have also revealed lithospheric mantle reflectors, which are thought to represent fossil, possibly Palaeoproterozoic, subduction zones (Warner et al 1996;Snyder, England & McBride, 1997).…”
Section: A Laurentian Basementmentioning
confidence: 99%
“…The continental blocks are thinned a little from the presumed original continental crustal thickness of 30-32 km found beneath nearby Ireland and northern Britain (e.g. Barton 1992;Landes et al 2005;Tomlinson et al 2006). The seismic velocity of the Hatton Bank and Fugloy Ridge continental blocks averages 6.7 km s 21 in the lower crust, which is typical of the velocity of continental crust beneath the UK well away from the oceanic rift.…”
Section: Crustal Velocity Modelsmentioning
confidence: 99%